2007
DOI: 10.1111/j.1945-5100.2007.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective release of D and 13C from insoluble organic matter of the Murchison meteorite by impact shock

Abstract: Abstract-We performed shock-recovery experiments on insoluble organic matter (IOM) purified from the Murchison meteorite, and determined the abundances and isotope ratios of hydrogen and carbon in the shocked IOM sample. We also performed shock experiments on type III kerogen and compared the results of these experiments with the experimental results regarding IOM.The shock selectively released D and 13 C from the IOM, while it preferably released H and 12 C from the kerogen. The release of these elements from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Because the dD values of the residues result from mixing of the pyrolysates and the thermally stable components, the thermally stable components should have lower dD values than the residues (e.g., +734&). Mimura et al (2007) reported that a shocked IOM sample had the low dD value of +235&. Thus, it is possible that the thermally stable parts have much smaller dD values than the bulk IOM.…”
Section: Hydrogen Isotopic Featuresmentioning
confidence: 93%
See 3 more Smart Citations
“…Because the dD values of the residues result from mixing of the pyrolysates and the thermally stable components, the thermally stable components should have lower dD values than the residues (e.g., +734&). Mimura et al (2007) reported that a shocked IOM sample had the low dD value of +235&. Thus, it is possible that the thermally stable parts have much smaller dD values than the bulk IOM.…”
Section: Hydrogen Isotopic Featuresmentioning
confidence: 93%
“…Other possible reactions are irradiation and shock reactions, which occur ubiquitously in space. The irradiation of organic mixtures produces carbon isotope heterogeneity (Sephton et al, 2004), while shock reactions effectively decrease the hydrogen isotope values of the IOM (Mimura et al, 2007). It is highly plausible that the product had been affected by these reactions before forming the meteorite.…”
Section: Formation In Interstellar Environmentsmentioning
confidence: 98%
See 2 more Smart Citations
“…One way to dilute isotopic enrichments is through the partial pyrolysis of the organic carrier phase during impact induced shock heating. For example, Mimura et al (2007) recently demonstrated the selective release of deuterium from Murchison (CM2) insoluble organic matter by shock impact. This illustrates the fundamental point that all cometary particles collected by Stardust will have experienced a significant thermal pulse during impact.…”
Section: Thermal Alteration Effects During Capture?mentioning
confidence: 99%